Association of Body Weight with the Risk for Malignancies in Hospitalized Patients with or without Diabetes Mellitus in Taiwan. (January 2014) - Hsieh, Sheng-Hwu; Chiou, Wen-Ko; Wang, Ming-Hsu; Lin, Jen-Der
Background: The purpose of this study was to determine the risk for cancers in patients with and without type 2 diabetes mellitus (DM) stratified by body mass index (BMI). Methods: Patients hospitalized from January 2000 to December 2010 with a diagnosis of malignant neoplasm ( International Classification of Diseases, Ninth Revision, codes 140-208.91) were included. Diabetes mellitus was defined as a fasting blood glucose of 126 mg/dL or greater or a postprandial blood glucose of 200 mg/dL or greater. The patients were categorized according to BMI criteria for Asians: normal weight, BMI of less than 24 kg/m 2 ; overweight, BMI of greater than 24 kg/m 2 ; and obese, BMI of greater than 27 kg/m 2 . Results: A total of 42, 229 patients were included, of which 24, 884 (59%) were normal weight, 10, 096 (24%) were overweight, and 7, 249 (17%) were obese. There were 4, 195 (16.9%), 2, 056 (20.4%), and 1, 625 (22.4%) patients with DM in the normal weight, overweight, and obese groups, respectively. Regardless of weight, the diabetic patients were more likely to have pancreas, liver, urinary tract, prostate, skin, hematological, lung, secondary, and gastric malignancies but were less likely to have cervical, oropharyngeal, nasopharyngeal, breast, or thyroid cancer. Regardless of sex or the presence or the absence of DM, the patients with more than 1 malignancy were more likely to die than were those with only 1 malignancy. Furthermore, the obese diabetic patients had higher mortality than did the obese nondiabetic patients with the same number of cancers. Conclusions: Regardless of weight category (normal, overweight, or obese), diabetic patients are more likely to have pancreas, liver, urinary tract, prostate, skin, hematological, lung, secondary, and gastric malignancies. Diabetic patients may benefit from increased surveillance for these cancers.